1989
DOI: 10.1152/ajpcell.1989.256.2.c288
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine-induced intracellular acidosis in rabbit salivary gland acinar cells

Abstract: Intracellular pH (pHi) was measured in acini isolated from rabbit mandibular salivary glands using the fluorescent pH-sensitive probe 2,7-bis(carboxyethyl)-5(6)-carboxyfluorescein (BCECF). Resting pHi was estimated to be 7.13 +/- 0.01 (mean +/- SE of 29 experiments). Stimulation with acetylcholine (ACh) caused an intracellular acidosis followed by a return of pHi toward the control value with a half time of approximately 3 min. The intracellular acidosis was dose dependent and could be abolished by pretreatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
43
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 1 publication
9
43
0
Order By: Relevance
“…The demonstration that the mechanism which caused the acidosis is independent of the presence of Na+ eliminates the possibility that the HCO3-efflux which underlies the acidosis could be mediated by a Na+-3HCO3-co-transport mechanism similar to that described in mammalian renal epithelia (Yoshitomi, Burckhardt & Fromter, 1985;Soleimani, Grassl & Aronson, 1987). This in turn indirectly supports our previous conclusion that HCO3-efflux probably takes place through non-specific anion channels (Lau et al 1989;Brown et al 1989b). Figure 3 also shows that following the acidosis pHi recovered to the control (pre-ACh stimulation) value in acini equilibrated in control or Na+-free (Li+) medium, although recovery was significantly slower in Na+-free (Li+) medium (Table 2).…”
Section: Effect Of Na+-free Conditions On Acetylcholine-evoked Changesupporting
confidence: 90%
See 4 more Smart Citations
“…The demonstration that the mechanism which caused the acidosis is independent of the presence of Na+ eliminates the possibility that the HCO3-efflux which underlies the acidosis could be mediated by a Na+-3HCO3-co-transport mechanism similar to that described in mammalian renal epithelia (Yoshitomi, Burckhardt & Fromter, 1985;Soleimani, Grassl & Aronson, 1987). This in turn indirectly supports our previous conclusion that HCO3-efflux probably takes place through non-specific anion channels (Lau et al 1989;Brown et al 1989b). Figure 3 also shows that following the acidosis pHi recovered to the control (pre-ACh stimulation) value in acini equilibrated in control or Na+-free (Li+) medium, although recovery was significantly slower in Na+-free (Li+) medium (Table 2).…”
Section: Effect Of Na+-free Conditions On Acetylcholine-evoked Changesupporting
confidence: 90%
“…We have previously shown that muscarinic stimulation of rabbit mandibular gland acinar cells evokes an intracellular acidosis followed by a recovery of pH1 towards control levels (Lau et al 1989;Brown et al 1989 b). The acidosis appears to be the result of HCO3-efflux from the cell, while the subsequent recovery of pH, may be mediated by Na+-H+ exchange since it is amiloride sensitive (Lau et al 1989;Brown et al 1989 b).…”
Section: Effect Of Na+-free Conditions On Acetylcholine-evoked Changementioning
confidence: 91%
See 3 more Smart Citations